1986
DOI: 10.7164/antibiotics.39.1160
|View full text |Cite
|
Sign up to set email alerts
|

Studies on lipoxygenase inhibitors. II KF8940 (2-n-heptyl-4-hydroxyquinoline-N-oxide), a potent and selective inhibitor of 5-lipoxygenase, produced by Pseudomonas methanica.

Abstract: Pseudomonas methanica KY4634 was found to produce 5-lipoxygenase inhibitor designated KF8940, MY12-62a and MY12-62c. The inhibitors were purified by solvent extraction, silica gel column chromatography, reversed-phase low pressure liquid chromatography and crystallization. The chemical structures of KF8940, MY12-62a and MY12-62c were determined to be 2-n-heptyl-4-hydroxyquinoline-N-oxide, 2-n-heptyl-4-hydroxyquinoline and 3-n-heptyl-3-hydroxy-1,2,3,4-tetrahydroquinoline-2,4-diore, respectively, on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…A series of chemoecological studies of P. aeruginosa has uncovered multifunctional roles of this quinolone class as antibacterial, antifungal, iron-chelating, and autoinducer agents to assist the survival of the producing organisms [ 32 ]. Additionally, drug discovery attempts have revealed 5-lipoxygenase inhibitory activity [ 33 ], plant-growth promoting activity [ 32 , 34 ], and IGF-dependent cell-specific cytotoxicity [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A series of chemoecological studies of P. aeruginosa has uncovered multifunctional roles of this quinolone class as antibacterial, antifungal, iron-chelating, and autoinducer agents to assist the survival of the producing organisms [ 32 ]. Additionally, drug discovery attempts have revealed 5-lipoxygenase inhibitory activity [ 33 ], plant-growth promoting activity [ 32 , 34 ], and IGF-dependent cell-specific cytotoxicity [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, P. aeruginosa express a number of fatty acid metabolizing enzymes including dioxygenases, hydroperoxide isomerases, and arachidonate 15-lipoxygenase (LoxA; contribution to the formation of 15-HETE) [76, 77] that may directly contribute to the oxygenation of fatty acids in the CF airway [76, 78] and contribute to the virulence and airway persistence of the organism [79]. One report has revealed that P. aeruginosa may be a source of secreted inhibitors of 5-lipoxygenase [80]. Moreover, a recent study has identified an epoxide hydrolase produced by P. aeruginosa [81] that could potentially metabolize epoxide-based oxylipins to the corresponding diols which compromise the functions of these anti-inflammatory oxylipins in the CF RT.…”
Section: Discussionmentioning
confidence: 99%
“…In the Russian literature, these compounds are named psevdans; Roman numerals indicating the chain lengths [138]. Spectroscopic and degradation studies established the presence of several 2-alk(en)yl-quinolones-4 (23) [69][70][71] and of their N-hydroxy derivatives (24) (also formulated in the tautomeric forms as 4-hydroxy quinoline (Noxides) [69,71,72] all of which show pronounced antibacterial activity. Pseudomonas aeruginosa seems also to produce 2-n-heptyl-3-hydroxy quinolone-4 [139].…”
Section: @Ch3mentioning
confidence: 99%
“…Pseudomonas aeruginosa seems also to produce 2-n-heptyl-3-hydroxy quinolone-4 [139]. In addition, 3-n-heptyl-and 3-n-nonyl-3-hydroxy-1,2,3,4-tetra-hydroquinoline-2,4-dione was found (25) [71,74]. From the data given in [68], a mixture of them could be Pyo IV.…”
Section: @Ch3mentioning
confidence: 99%